2015
DOI: 10.1080/10408398.2015.1018987
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Red Yeast Rice Dietary Supplement on Blood Pressure, Lipid Profile and C-reactive Protein in Hypertension: A Systematic Review

Abstract: Interest is increasing regarding the potential health effects of red yeast rice (RYR) consumption, which is described as a "natural statin" in China. This review aims to evaluate the efficacy of RYR on blood pressure (BP), lipid profile, and C-reactive protein (CRP) in treating hypertension. Seven electronic databases including the Cochrane Central Register of Controlled Trials, EMBASE, PubMed, the Chinese National Knowledge Infrastructure (CNKI), the Chinese Scientific Journal Database (VIP), the Chinese Biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…Additional clinical trials with RYR and meta-analyses [112e115] have reported similar results in different study populations (Table 7). In a meta-analysis of thirteen randomized placebo-controlled trials [113] including over [112,114,115], confirming the cholesterollowering efficacy of RYR and its good safety profile. In particular, a meta-analysis by Gerard et al [114] showed that the incidence of muscle, hepatic and renal adverse events was comparable between RYR and placebo; overall, the clinical relevance of the possible adverse events of RYR were moderate, but the incomplete reporting of safety data in most individual trials included in this metaanalysis must also be underlined [114].…”
Section: Red Yeast Ricementioning
confidence: 92%
“…Additional clinical trials with RYR and meta-analyses [112e115] have reported similar results in different study populations (Table 7). In a meta-analysis of thirteen randomized placebo-controlled trials [113] including over [112,114,115], confirming the cholesterollowering efficacy of RYR and its good safety profile. In particular, a meta-analysis by Gerard et al [114] showed that the incidence of muscle, hepatic and renal adverse events was comparable between RYR and placebo; overall, the clinical relevance of the possible adverse events of RYR were moderate, but the incomplete reporting of safety data in most individual trials included in this metaanalysis must also be underlined [114].…”
Section: Red Yeast Ricementioning
confidence: 92%
“…RYR (Monascus purpureus) is a fermented product of rice that contains monocolins, which inhibit cholesterol synthesis via HMG-CoA reductase, and thus has "statin-like" properties. 1,69,70 RYR also contains sterols, isoflavones, and MUFA. At 2400 mg/day, LDL-C is reduced by 22% (P < 0.001), and TG falls by 12%, with little change in HDL-C. 1,69,70 A metaanalysis by Xiong showed that RYR reduced LDL by 17.6% (P < 0.001) and increased HDL by 4.2% (P < 0.001) at doses of up to 1600 mg/day.…”
Section: Ryrmentioning
confidence: 99%
“…Different reports confirmed that RYR significantly lowered both LDL cholesterol and total cholesterol. Effects on triglycerides and HDL cholesterol were also observed in some studies . Compared with statins, red rice yeast was shown to have a similar efficacy in lowering serum cholesterol levels; moreover, the extract of RYR does not seem to have the collateral adverse effects, for example, myalgia, with respect to other commercially available statins .…”
Section: Introductionmentioning
confidence: 99%
“…Effects on triglycerides and HDL cholesterol were also observed in some studies. [12][13][14] Compared with statins, red rice yeast was shown to have a similar efficacy in lowering serum cholesterol levels; moreover, the extract of RYR does not seem to have the collateral adverse effects, for example, myalgia, with respect to other commercially available statins. [15][16][17][18][19] The European Food Safety Authority permits the use of monacolin K from RYR extract in dietary supplement preparations at maximum 10 mg for day, 20 while in the United States, the Food and Drug Administration considers monacolin K an unapproved drug, and its use is banned in the dietary supplements.…”
Section: Introductionmentioning
confidence: 99%